Integrated Electoral Cartelization: Indonesia’s New Cartelization Model Through Competitive Intervention in 2024 Regional Head Elections - Dian Jayanto (Universitas Negeri Semarang, 2025)
The study examines Integrated Electoral Cartelization as a new model of political cartelization in Indonesia through intervention conducted by the Advanced Indonesia Coalition (Koalisi Indonesia Maju) during the 2 24 regional head elections across five strategic provinces: Jakarta, Banten, West Java, Central Java, and East Java. The research aims to explain institutional patterns of cartel coordination shaping candidate nomination processes prior to electoral competition. A qualitative case study approach was applied through a systematic review of peer-reviewed journal publications and verified online media documentation addressing coalition coordination during the 2 24 regional head elections. Data analysis followed the interactive analytical framework developed by Miles, Huberman, and Saldaña through sequential procedures consisting of data condensation, data display, and conclusion drawing. Findings identify three institutional coordination patterns: centralized candidate nomination determined by national political elites within coalition command structures; co-optation of former opposition parties to strengthen electoral alignment and cartel consolidation; and exclusion of political parties outside cartel arrangements from meaningful participation in candidate nomination processes and competitive electoral arenas. The Integrated Electoral Cartelization framework demonstrates transformation of cartel politics toward centralized oligarchic coordination structures regulating candidate selection and coalition alignment prior to electoral competition, contributing conceptual advancement to cartel party theory and providing analytical insight into coalition governance dynamics within subnational democratic institutions in Indonesia.